Concise Review: TLR Pathway-miRNA Interplay in Mesenchymal Stromal Cells: Regulatory Roles and Therapeutic Directions. (13th October 2018) - Abdi, Jahangir; Rashedi, Iran; Keating, Armand
Abstract : Mesenchymal stromal cells (MSCs) deploy Toll-like receptors (TLRs) to respond to exogenous and endogenous signals. Activation of TLR pathways in MSCs alters their inflammatory profile and immunomodulatory effects on cells from both the innate and adaptive immune systems. Micro-RNAs (miRNAs), whose expression is modulated by TLR activation, can regulate inflammatory responses by targeting components of the TLR signaling pathways either in MSCs or in the cells with which they interact. Here, we review how the miRNA-TLR pathway axis can regulate the immunomodulatory functions of MSCs, including their interactions with monocytes/macrophages and natural killer cells, and discuss the therapeutic implications for MSC-based therapies. Abstract : TLR pathways-microRNA interplay in MSCs affects the phenotype of MSCs and the interacting microenvironment including immune cells. TLR-responding microRNA may also transfer to the new cells via extracellular vesicles released by MSCs.